Analisis Sistem Pengelolaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan dalam Meningkatkan Pendapatan di Kabupaten Tambrauw - Bidangan, Marthen Bikarto; Longkutoy, Meyta; Sinay, Philipus (CV. Creative Tugu Pena, 2022)
This study aims to analyze the land and building tax management system in rural and urban areas, its effect on local revenue in Tambrauw Regency and the inhibiting factors that affect the management of PBB in increasing PAD in Tambrauw Regency. This type of research is field research using a descriptive qualitative approach, namely explaining the management of rural and urban land and building taxes at the Regional Tax and Retribution Management Agency of Tambrauw Regency by conducting interviews, observations, and document review. This research was conducted at the office of the Regional Tax and Retribution Management Agency, Tambrauw Regency. This study uses primary and secondary data types. The results of the study indicate that the Regional Tax and Levy Management Agency of Tambrauw Regency in managing rural and urban land and building taxes to increase local revenue based on three management functions, namely planning, implementation, and supervision has not been maximized, and the inhibiting factors that affect the management of PBB in increasing PAD in Tambrauw Regency, piled on obstacles that occur because it is known that there are two inhibiting factors, namely internal and external factors, namely as follows: a) Internal, namely regulations (Perda, Perbup, SOP) that are not yet good and incomplete, limited supporting facilities, such as operational vehicles, and performance of ASN OPD BPPRD that is not yet maximal, b) External, namely coordination between OPD and other stakeholders that is not yet effective, understanding of taxpayers is low, and commitment and coordination of regional leaders is weak. Keywords: Tax Management System, Tax Management Analysis, Increase Income